The Growth on the Maximum Modulus of Double Dirichlet Series - Yong-Qin Cui; Hong-Yan Xu; Na Li (Journal of Function Spaces)
The main purpose of this paper is to investigate the growth of several entire functions represented by double Dirichlet series of finite logarithmic order, h-order. Besides, we also study some properties on the maximum modulus of double Dirichlet series and its partial derivative. Our results are extension and improvement of previous results given by Huo and Liang.